Effects of Chicken Compost and KCl Fertilizer on Growth, Yield, Post-Harvest Quality of Sweet Corn and Soil Health - Darwin Habinsaran Pangaribuan; Sarno Sarno; Yessa Liliana; Sarah Bahriana (AGRIVITA, Journal of Agricultural Science, 2020)
This study aimed to determine the effects of chicken compost and KCl fertilizer application on the growth, yield, post-harvest quality of sweet corn (Zea mays L. var. saccharata), soil respiration and microbial population. The research was arranged according to a Factorial Random-Block Design consisting of two factors and three replications. The first factor was the dose of chicken compost (0 and 15 t/ha) and the second the dose of KCl fertilizer (0, 50, 100 and 150 kg/ha). The results showed that chicken compost stimulated the growth, yield, postharvest quality of sweet corn, respiration, and microbial activity of soil. KCl fertilizer increased SPAD values linearly and quadratically chlorophyll pigment, β-carotene, yield components, and yield. KCl fertilizer did not affect soil respiration, fungi, or bacteria populations. The use of chicken compost reduced the need for KCl fertilization by 25%. Therefore, the integration of organic and inorganic fertilizers are recommended to be applied by farmers in the tropics.